Effects of copper sulfate and zinc oxide on weanling pig growth and plasma mineral levels - N W Shelton; Michael D Tokach; Joel M DeRouchey; G M Hill; R G Amachawadi; Tiruvoor G Nagaraja; Jim L Nelssen; Robert D Goodband; Steven S Dritz (Kansas Agricultural Experiment Station Research Reports, 2009)
A total of 216 weanling pigs (PIC TR4 × 1050, initially 13.6 lb and 21 d of age) were used in a 42-d growth trial to compare the effects of supplemental zinc and copper and changing mineral regimens on growth performance and plasma mineral levels. The 6 dietary treatments included a 2 × 2 factorial arrangement with main effects of added copper from copper sulfate (0 or 125 ppm) and added zinc from zinc oxide (0 or 3,000 ppm from d 0 to 14 and 0 or 2,000 ppm from d 14 to 42). For the final 2 treatments, either zinc oxide alone or the combinations of zinc and copper were fed from d 0 to 14, with copper sulfate fed from d 14 to 42. There were 6 pens per treatment with 6 pigs per pen. All diets were supplemented with an additional 165 ppm zinc and 16.5 ppm copper from the trace mineral premix. Plasma was collected from 2 pigs per pen on d 14 and 42. From d 0 to 14, ADG, ADFI, and F/G were improved (P<0.04) with the addition of dietary zinc. Copper supplementation also tended to increase (P<0.07) ADFI from d 0 to 14. From d 14 to 42, added copper increased (P<0.003) ADG and ADFI. Over the entire trial, continuous supplemental zinc increased (P<0.03) ADG and tended to increase (P<0.09) ADFI. Dietary copper also increased (P<0.004) ADG and ADFI when fed from d 0 to 42. The most advantageous values for ADG and ADFI were seen in the treatment containing high levels of zinc from d 0 to 14 and high copper levels from d 14 to 42. The addition of either zinc or copper increased (P<0.02) feed cost per pound of gain. However, income over feed cost was improved (P<0.006) with the addition of copper, with the greatest value obtained when high zinc was fed from d 0 to 14 and high copper was fed from d 14 to 42. Plasma zinc levels were increased (P<0.001) with zinc supplementation on d 14. These results indicate the optimal mineral regimen was supplementing zinc oxide from d 0 to 14 and copper sulfate from d 14 to 42.; Swine Day, Manhattan, KS, November 19, 2009
Keywords: Swine day; 2009; Kansas Agricultural Experiment Station contribution; no. 10-014-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 1020; Copper; Growth promotion; Zinc; Swine